Perfluorocarbon emulsion enhances MR-ARFI displacement and temperature in vitro: Evaluating the response with MRI, NMR, and hydrophone - Holman, Ryan; Lorton, Orane; Guillemin, Pauline C.; Desgranges, Stéphane; Santini, Francesco; Preso, Davide Bernardo; Farhat, Mohamed; Contino-Pépin, Christiane; Salomir, Rares (Frontiers in Oncology, 2023)
Sonosensitive perfluorocarbon F8TAC18-PFOB emulsion is under development to enhance heating, increase thermal contrast, and reduce treatment times during focused ultrasound tumor ablation of highly perfused tissue. The emulsion previously showed enhanced heating during ex vivo and in vitro studies. Experiments were designed to observe the response in additional scenarios by varying focused ultrasound conditions, emulsion concentrations, and surfactants. Most notably, changes acoustic absorption were assessed with MR-ARFI. Phantoms were developed to have thermal, elastic, and relaxometry properties similar to those of ex vivo pig tissue. The phantoms were embedded with varying amounts of F8TAC18-PFOB emulsion or lecithin-PFOB emulsion, between about 0.0-0.3% v:w, in 0.05% v:w increments. MR-ARFI measurements were performed using a FLASH-ARFI-MRT sequence to obtain simultaneous displacement and temperature measurements. A Fabry-Perot hydrophone was utilized to observe the acoustic emissions. Susceptibility-weighted imaging and relaxometry mapping were performed to observe concentration-dependent effects. 19F diffusion ordered spectroscopy NMR was used to measure the diffusion coefficient. Increased displacement and temperature were observed with higher emulsion concentration. In rigid MR-ARFI phantoms, a linear response was observed with low-duty cycle MR-ARFI sonications and a mono-exponential saturating response was observed with sustained sonications. The emulsifiers did not have a significant effect on acoustic absorption in rigid gels. Stable cavitation might also contribute to enhanced heating.